63‐3: Student Paper: High‐Directivity Emitting Pixel Devices for Advanced Display Applications. Issue 1 (28th June 2022) - Chen, Po-Jui; Chang, Chi-Jui; Lee, Wei-Kai; Cyue, Zih-Rou; Yu, Li-Yu; Lin, Hoang Yan; Su, Guo-Dung J.; Chen, Chung-Chia; Lin, Wan-Yu; Kwak, B. Leo; Visser, Robert Jan; Wu, Chung-Chih
Abstract : For advanced displays like AR or light‐field 3D displays, highly narrow emission patterns (high directivity) from display pixels are highly desired for achieving angular resolutions or higher optical efficiency. In this work, we report an OLED pixel device architecture that can generate highly directional emission and yet also keep decent efficiency. By combining with other optical elements and optical systems, such OLED pixel device architecture shall find use in advanced displays.